ИСҲАҚХАН ИБРАТТЫҢ ИБРАТЛЫ ӨМИРИ ҲӘМ АҒАРТЫЎШЫЛЫҚ ХЫЗМЕТЛЕРИ - Сейтмуратов, Қ. (FAN va JAMIYAT, 2025)
The article talks about the educational-Jadid activities and pedagogical views of Ishakhon Ibrat, a famous writer-educator.